KOMPETENSI PEKERJA DI ERA INDUSTRI 4.0 - Sri Rizki Safitri (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Industry 4.0 is a term that represents the radical transformation of industry resulting from the integration of emerging technologies. Industry 4.0 is demanding changes to the labor market, explicitly requiring training. However, to achieve this, manufacturers must overcome several obstacles, such as the lack of quality competencies to develop and manage various high-tech systems Workers who have competencies and skills will be accepted in the world of work of the industrial era 4.0. To improve worker competence, companies must also provide training programs for their workers to adapt to new demands. It is expected that the company periodically reviews the competencies and technologies needed in the business world. And the company helps find solutions in developing worker competence in the industrial era 4.0.